Fibrinogen, Fibrin and Crosslinking in Aging Arterial Thrombi - McBane, Robert D., II; Ford, Monique A. P.; Karnicki, Krzysztof; Stewart, MaryLou; Owen, Whyte G. (Thrombosis and Haemostasis, 2000)
The assumption that fibrin and crosslinked fibrin impart irreversibility to arterial thrombi is explored with procedure developed for measuring changes in platelet function, morphology and fibrinogen metabolism in aging occlusive thrombi, in which the condition of stasis is imposed uniformly. Arterial thrombi containing autologous 111In labeled platelets were generated in vivo by bilateral mechanical injury of porcine carotid arteries. Vessels containing the platelet-rich thrombi were harvested and incubated intact (37° C) for intervals ranging from 30 min to 12 h. The isolated vessels were then bisected and agitated in culture medium containing tick anticoagulant and hirudin for 60 min. Disaggregated platelets were evaluated for yield (from 111In radioactivity) viability (dense body ATP secretion) and morphology (electron microscopy). Western analysis of fibrin(ogen) in thrombus extracts was performed using anti-fibrinogen Bβ- and γ-chain monoclonal antibodies for thrombi at each time point. A stable recovery of nearly 50% of platelets was observed during 12 h of thrombus aging. As thrombi aged, viability of disaggregated platelets gradually decreased with platelet necrosis the predominant feature beyond 6 h. By western analysis of thrombus extracts, nearly 50% of fibrinogen was cleaved to fibrin and extensively crosslinked within 30 min of injury with no evidence of fibrinolysis. With the exception of a declining proportion of γ-monomer, these features remain relatively constant during 12 h of thrombus maturation. It is concluded that neither fibrin nor crosslinked fibrin are dominant factors imparting cohesion within platelet thrombi. Furthermore, under conditions of complete arterial occlusion imposed by this experimental design, there is no evidence of endogenous fibrinolysis.
Keywords: Fibrin; crosslinked fibrin; fibrinolysis; platelets; arterial thrombosis